2010
DOI: 10.1111/j.1365-3083.2010.02374.x
|View full text |Cite
|
Sign up to set email alerts
|

The Treg/Th17 Imbalance in Patients with Idiopathic Dilated Cardiomyopathy

et al.

Abstract: To assess whether Treg/Th17 balance was broken in patients with idiopathic dilated cardiomyopathy (DCM). We studied 25 patients who were diagnosed as idiopathic DCM (18 men and seven women, mean age 35.6 ± 5.2) and 25 normal persons (18 men and seven women, mean age 33.8 ± 4.9). Then, we detected Treg/Th17 functions on different levels including cell frequencies, related cytokine secretion and key transcription factors in patients with idiopathic DCM and controls. The results demonstrated that patients with id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 29 publications
4
27
0
Order By: Relevance
“…On the other hand, the ratio of Treg/Th17 cells was lower in patients with DCM than that in healthy donors. These findings were in agreement with those of study from Wang et al [12]. Moreover, we demonstrated the elevation of RGC-32 levels was accompanied by the increased frequency of Th17 cells.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…On the other hand, the ratio of Treg/Th17 cells was lower in patients with DCM than that in healthy donors. These findings were in agreement with those of study from Wang et al [12]. Moreover, we demonstrated the elevation of RGC-32 levels was accompanied by the increased frequency of Th17 cells.…”
Section: Discussionsupporting
confidence: 83%
“…Interestingly, further work by Chen et al demonstrated that in autoimmune myocarditis a lower proportion of Treg cells was associated with a greater Th17 response and more severe autoimmune myocarditis [16]. An imbalance between Treg and Th17 cells has recently been observed in idiopathic DCM [12,17]. In the study by Rus et al, the proportion of Th17 was significantly decreased in RGC-32-deficient CD4 + T cells under Th17 polarizing conditions [18].…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Tregs are decreased and have impaired functionality in DCM [26, 40]. Additionally, cardiac-specific auto-antibodies that have been reported in DCM patients showed a pathogenic role in cardiac dilatation and dysfunction.…”
Section: Discussionmentioning
confidence: 99%